Characterisation of landraces of drumstick (Moringa oleifera Lam.) - Resmi D S (Department of Olericulture, College of Agriculture, 2004)
The present investigation on “Characterisation of landraces of drumstick (Moringa oleifera Lam.)” was carried out at the Department of Olericulture and Department of Plant Biotechnology, College of Agriculture, Vellayani during 2002-2004. The experiment was carried out using 28 diverse accessions of drumstick collected from different agro climatic situations particularly from southern parts of Kerala. The objective of the study was to assess the extent of genetic variability in the landraces of drumstick using morphological characters and Random Amplified Polymorphic DNA (RAPD) markers. A survey was conducted to identify the morphologically distinct drumstick trees in the different regions of Kerala. Biometrical observations were recorded from the selected plants by conducting field visits. Morphological data was collected on vegetative characters, flowering characters, fruit characters, quality characters and reaction towards pest and disease incidence. Planting materials of each accession were also collected from the identified plants and planted them at the Department of Olericulture for further investigation and conservation. All the accessions showed variation for the morphological characters studied. Height varied from 5.0-12.5 m. The leaf length, width and weight showed variability with a mean value of 44.58 cm, 33.79 cm and 5.17 g respectively. Accessions MO 13, MO 24, MO 26 recorded 3 flowering peaks per year whereas all the remaining accessions showed two peak flowering except MO 16 which showed only one peak per year. The number of flowers per inflorescence varied from 65.23 (MO 28) to 25.4 (MO 22). The fruits per plant varied from 174 (MO 16) – 612 (MO 24) and the fruit yield ranged from 8.94 kg (MO 8) to 70.46 kg (MO 28). The range of values for the quality characters were 8107.86 (MO 1) to 13,215.79 I. U. (MO 26) for vitamin A in leaf, 94.59 (MO 25) to 184.74 (MO 10) for vitamin A in fruit, 175.21 (MO 5) to 225.56 mg / 100 g (MO 18) for vitamin C in leaf and 87.5 (MO 3) to 129.16 mg / 100 g (MO 18) for vitamin C in fruit. The leaves of MO 13 and fruits of MO 10 were organoleptically superior compared to others studied. A severe attack of fruit rot was noted in accession MO10 and MO 13. The fungus was identified as Fusarium pallidoroseum (Cooke) Sacc. All the accessions were observed for the incidence of bud borer and hairy caterpillar and all of them were equally susceptible. Based on important morphological characters, overall ranking was done in all the accessions and accession MO 26 and MO 28 were superior compared to others. Molecular characterisation of 25 accessions of drumstick which were identified distinct as per morphological characterisation was done. Out of 35 primers tested, 19 yielded amplification products. Five primers showed polymorphism among the accessions and finally three primers were selected (OPA 10, OPA 13 and OPB 7) for RAPD analysis. These primers gave 18 scorable bands with an average of 6 bands per primer. Dendrogram was generated by UPGMA cluster analysis. At about 65 per cent similarity index, the accessions formed five clusters. Accessions MO 1, MO 9, MO 10, MO 13, MO 7, MO 20, MO 21, MO 4, MO 12, MO 14, MO 17, MO 25, MO 26 and MO 27 grouped together to form the largest cluster. Accessions MO 7 and MO 20 which showed a similarity index value of 1.00 belonged to different locations. Accessions MO 12 and MO 14 were having a similarity index value of 1.00, but they also belonged to different geographical locations. Accessions MO 3, MO 22, MO 15, MO 23 and MO 24 grouped together to form cluster II. Accessions MO 22, MO 23, MO 24 belonged to same location, but they were not morphologically similar. Accession MO 28 and accession MO 2 formed each separate cluster respectively. Accession MO 28 was already distinct as superior as morphological ranking. Accessions MO 6, MO 18, MO 11 and MO 16 together formed cluster V. Accessions MO 11 and MO 16 were from adjacent locations and showed a similarity index of 1.00. Cluster formation was not fully in agreement with geographical locations. Morphological studies had shown that MO 26 and MO 28 were superior when compared to others. Molecular studies also confirms the distinctness of MO 28 and it can be used in further breeding programmes. The present study using morphological characters and RAPD markers have shown considerable variability in the available landraces. However, accessions with broader genetic base have to be studied with more number of primers for getting accurate results.